Applications of leverenz theorem in univalent functions / Siti Aishah Sheikh Abdullah - Sheikh Abdullah, Siti Aishah (2002)
Leverenz theorem is stated and equivalent finite form is then obtained. Examples are then illustrated to show some of the applications of the theorem. It was found that the results obtained are analogous to the some of the well-known inequalities for class P and class B.